CORRELATIONS BETWEEN THE ACTIVITY OF SOIL ENZYMES AND THEIR AGROCHEMICAL PROPERTIES (Modern American Journal of Biological and Environmental Sciences, 2025)
This article analyzes the enzymatic relationships between the enzymatic activity of irrigated serozem-meadow soils of various degrees of salinity and their agrochemical properties, common in the Khavast district. The data obtained showed that due to the unfavorable climatic conditions in the research area, varying degrees of soil salinity and low organic matter content, a low degree of enzymatic activity is observed.